Rescue Excavations at the Parthenion City Site in 2020 - Vakhtina, Marina; Solovyev, Sergey; Vakhoneev, Viktor; Chetverkina, Ekaterina (Hyperboreus, 2024)
The article is devoted to the results of the archaeological rescue excavations of ancient Parthenion and its necropolis conducted in 2020 by the rescue archaeological expedition of the Institute for the History of Material Culture RAS. The need for urgent implementation of these works was caused by the construction of the supply water line, whose route crossed a protective zone of the site. At the city site, the studies took place on an area of 520 m2; at the necropolis, they were conducted on an area of 420 m2. During the excavations, the remains of urban buildings of the Hellenistic Period – various aboveground objects and utility pits – were unearthed. One of the most interesting of the revealed buildings is the winery, the first one known on this site. A representative collection of archaeological material, mostly belonging to the Hellenistic period, was found. Worth noting among the individual finds is a fragment of a mold for fabricating relief bowls with a ΔΗΜΗ[ΤΡΙΟΥ] stamp. It testifies to the existence of a workshop there. In the examined area of the southwestern Parthenion necropolis, three graves from the Hellenistic Age were found. The first was made in a pit, lined with limestone slabs; the second was situated in a pit, embedded in bed soil rock; the third was found in a simple ground pit. Beads of different types, fragments of terracotta statuettes, and a bronze Bosporan coin were found among the grave goods. The grave structures and the rite show similarities with the grave complexes of the Bosporan necropoleis. The materials found during the rescue excavations of Parthenion are of great importance for the reconstruction of the appearance of the ancient city and the economic activities of its inhabitants in the Hellenistic period.